Regional Mapping of Smoking Behavior Determinant of Indonesia’s High School Students (Analysis Of Global School-Based Health Survey 2015) - Azzah Farah Fadiyah; Eri Wahyuningsih; Aisyah Apriliciciliana Aryani (Kesmas Indonesia, 2021)
Indonesian Global School-based Health Survey (GSHS) 2015 was divided into three regions. The survey showed that main problem behavior among students was smoking. Cigarette contain dangerous substances that can cause diseases. This study was conducted to analyze regional mapping of smoking behavior determinant of Indonesia’s high school students based on Indonesian GSHS 2015. This study uses cross-sectional approach with logistic regression and descriptive design with geographic information system using classification function. 8.634 samples were selected by Probability Proportionate to Size method. The result showed that smoking behavior determinant were have been physically attacked (OR 2,03), have been bullied (OR 1,2), drug use (OR 9,8) and alcohol use (OR 13,4). Highest prevalence of students have been physically attacked and smoking was in Sumatera region (16%). Highest prevalence of students have been bullied and smoking was in Sumatera region (13,9%). Highest prevalence of students were drug use and smoking was in Sumatera region (93,3%). Highest prevalence of students were alcohol use and smoking was in Sumatra region (64%). Alcohol use was strongly associated with students’ smoking behavior. Each of the highest determinants of smoking was in Sumatera region. We advise students to avoid determinant of smoking behavior, especially alcohol use.